THE KATHERINE WATSON'S AMBITION TO EMPOWER FEMALE STUDENTS IN MIKE NEWELL'S MONA LISA SMILE (2003): A FEMINIST PERSPECTIVE - AYUNINGTYAS, PUTRI (2010)
This research paper elaborates Katherine Watson's ambition to empower female students in conservative college by art teacher, which are analyzed through Feminist Perspective. The objectives of the research are to analyze the movie based on its structural elements and to analyze the movie based on the Feminist analysis. In analyzing Mona Lisa Smile, the writer uses qualitative method and feminist perspective. The object of the study is Mike Newell's Mona Lisa Smile that was released in 19 December 2003, produced by Revolution studios and Colombia pictures. The data sources consist of primary data and secondary data sources. The primary data source is the movie Mona Lisa Smile itself and the secondary data sources are the other sources related to the analysis such as the author's biography, books of literary theory and feminism. The method of the data collection is purpose sampling. The technique of data analysis is descriptive. The outcome of the study shows in the following conclusions. First in this movie Mona Lisa Smile based on the structural analysis; the movie shows that the director was successful in integrating all structural elements of the movie into good unity, representing his criticism against the conservative college. Second, in this movie, Mike Newell wants to say that women have to struggle to get rights in her life, and women's right are not given but must be struggled for. And the last, this movie contains many facts that are revealed by Katherine Watson which reflect woman's right, woman's position, woman's role, and woman's participation in leading her life as an Art teacher in conservative college.